The effects of lifting straps on force applied during the power clean - Cowan, J.; DeBeliso, M. (International Journal of Sports Science, 2017)
Lifting straps (LS) are often used by individuals to aid in the execution of the power clean (PC) as they aid in the hand coupling with the lifting bar. PURPOSE: This study analyzed the PC exercise in regards to ground reaction force (GRF), rate of force development (RFD) and 1RM, both with and without lifting LS. METHODS: There were 13 participants in this study comprised of male high school basketball players with an age range of 13-17. All participants have had a minimum of one year of proper weight lifting training provided by a certified personal trainer, and experienced Olympic style weight lifter. The study used a repeated measures cross over study design where the participants performed two sets of two reps of the PC, both with and without LS. The athletes performed a dynamic warm-up followed by progressive sets of the PC at low intensity (50% of their 1RM). Following the dynamic warm-up and PC progression sets the participants performed two sets of two repetitions with and without LS at an intensity of 70% 1RM while standing on a force plate. The peak vertical GRF (Newtons-N) and RFD (N/second) were assessed for second pull of the PC. The peak GRF and RFD were compared between conditions with paired t-tests. The force plate collected data at a sampling rate of 1000 hertz and the subsequent data was filtered at 100 hertz. RESULTS: The 1RM PC with no LS was significantly lower (72.7±15.9 kgs*) than the 1RM PC with LS (79.0±18.4 kgs). Peak vertical GRF was significantly lower for the LS conditions (1953.3±450.7 N*) compared to the no LS conditions (2004.0±443.7 N) (p0.05). CONCLUSION: Within the parameters of this study, the use of lifting LS did improve PC 1RM. However, LS did not improve the ability to generate greater vertical GRF or RFD. Coaches should work with their athletes on an individual basis to determine if the use of LS would be advantageous when performing the PC.